Lane Detection Method Based on Recursive Binary Fitting (Journal of Fiber Bioengineering and Informatics, 2015)
This paper introduces a method of lane detection based on recursive binary fitting method of the lane\rdetection: First use canny edge detection algorithm to detect the edges on the basis of gray images, and\rthen scan the edge image from the left to the right and from the bottom to the top, we can extract the\rinner side of the lane edge of the interested region and dilate the lane by connecting some breakup, and\ron this basis and through the connected domain \fltering, to remove the one that does not conform to\rthe characteristics of binary image of lane. At last, we can get the lane by the recursive binary fitting\rmethod. The results show that the algorithm has good robustness and real-time performance.